PENGENALAN OLAHRAGA PENCAK SILAT DALAM MELESTARIKAN BUDAYA ASLI BANGSA INDONESIA - Nabihah, Marwa; Mulyadi, Acep; Irham, Irham (Universitas Islam 45 Bekasi, 2024)
Pencak silat is an integral part of Indonesia's rich culture which not only includes martial arts, but also the noble values ​​contained therein. Through the introduction of pencak silat sports at SDN Jayasampurna 03, the main aim of this activity is to introduce and preserve the original cultural heritage of the Indonesian nation, as well as forming students' overall character. Implementation methods include direct outreach and training to students, involving demonstrations, pair exercises, material collaboration, as well as discussion and reflection sessions. The results of this activity show that the students of SDN Jayasampurna 03 are able to understand, appreciate and practice the basic movements of pencak silat with high enthusiasm. In addition, they also benefit from developing physical, mental and social skills, as well as a deeper understanding of Indonesian culture. The suggestion for this activity is to continue and expand the pencak silat program into the school curriculum as a permanent and sustainable extracurricular activity. This will ensure that every student has the opportunity to engage in and benefit from this martial art, as well as ensuring that pencak silat education is improved comprehensively at all levels of education to respect the cultural heritage and noble values ​​contained within it.